2018
DOI: 10.3389/fmicb.2018.02401
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid LAMP-Based Method for Screening Poultry Samples for Campylobacter Without Enrichment

Abstract: Campylobacter is the most prominent bacterium associated with foodborne disease and the majority of human infection cases are attributed to chicken. Rapid methods capable of determining the Campylobacter status of poultry products in a short time are needed in today’s fast-paced food supply chain. In this study, we developed and evaluated an easy to perform, rapid and robust method for direct detection of Campylobacter in poultry carcasses based on loop-mediated isothermal DNA AMPlification (LAMP). The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
(21 reference statements)
0
15
1
Order By: Relevance
“…LODs of 1 CFU/reaction (corresponding to 50 CFU/ml) were observed for both C. jejuni and C. coli within 30 min of amplification (Figure 4). The optimized LAMP assay, in this study, showed better performance with lower LOD and shorter reaction time than previous reports (1.2–1.4 CFU and 5 CFU per reaction within 60 min) (Yamazaki et al, 2008; Romero and Cook, 2018).…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…LODs of 1 CFU/reaction (corresponding to 50 CFU/ml) were observed for both C. jejuni and C. coli within 30 min of amplification (Figure 4). The optimized LAMP assay, in this study, showed better performance with lower LOD and shorter reaction time than previous reports (1.2–1.4 CFU and 5 CFU per reaction within 60 min) (Yamazaki et al, 2008; Romero and Cook, 2018).…”
Section: Resultscontrasting
confidence: 44%
“…LAMP was developed for the detection of Campylobacter spp. in poultry samples such as meat, carcass swabs, and fecal samples (Yamazaki et al, 2008, 2009b; Sabike et al, 2016; Romero and Cook, 2018; Sabike and Yamazaki, 2019). To study the epidemiology of Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Performing 45 LAMP significantly increased the number of detected positive samples (from 74% to 82.5%, Table S2), with 10 1 CFU/g samples being detected after 4 h of enrichment (Figure 6a). In a study on artificially contaminated swabs, the limit of detection of 60 LAMP was reported between 10 3 and 10 4 CFU/swab [24]. In fact, with our protocol, the increase to 60 of the colorimetric LAMP resulted in the production of false positives, with a decrease in specificity (data not shown); however, the 30 or 45 protocol detected down to 10 3 CFU/g without enrichment.…”
Section: Discussionmentioning
confidence: 55%
“…Colorimetric LAMP assays were carried out using primers previously described by Zhuang et al [22] for Salmonella and by Romero et al [23,24] for Campylobacter spp. (Table 2).…”
Section: Colorimetric Lampmentioning
confidence: 99%
See 1 more Smart Citation